UNIVERSITY STUDENTS’ PERCEPTIONS TOWARD THE USE OF PODCASTS IN ENHANCING LISTENING SKILLS - Siti Fauziah; Faras Taufiqoh Nur Ainiyah; Naf'an Tarihoran (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
This study was motivated by the importance of utilizing digital media to enhance English listening skills. It aimed to investigate students’ perceptions of podcast use, the extent to which podcasts improve listening skills, the difficulties encountered, and their role in independent learning. This study employed a quantitative descriptive approach using a Likert-scale questionnaire distributed via Google Forms. A total of 37 respondents participated, but only 33 responses were analyzed. The data were analyzed using descriptive statistics in the form of mean scores. The results show that all indicators fall into the high category (3.5-4.1), indicating that podcasts have a positive impact on listening skills. However, students still experience difficulties related to vocabulary and speech rate. Overall, podcasts are effective as flexible learning media that support independent learning.